Setup for characterising the spectral responsivity of Fabry–Pérot-interferometer-based hyperspectral cameras. (10th October 2019) - Pekkala, Oskari; Pulli, Tomi; Kokka, Alexander; Ikonen, Erkki
Abstract: Hyperspectral cameras capture the spectral power distribution of the objects in the imaged view via dozens of narrow-band spectral channels of the camera. Knowledge of the spectral responsivity of the channels is essential when interpreting the acquired hyperspectral data and assessing its reliability. The spectral responsivity of the camera channels may vary within the image area. This paper presents a measurement setup and data analysis routine for characterising the spectral responsivity of a hyperspectral camera. This method was used to characterise the spectral responsivity of a Fabry–Pérot-interferometer-based hyperspectral camera. The characterisation method implemented in this study was able to reveal several channel leaks in the measured wavelength range. In the image area there is an approximately 1.5 nm shift in the channel wavelengths, and up to 10% variation in the channel bandwidths. The expanded uncertainties ( k = 2) for the measured channel bandwidths, sensitivities and wavelengths were 7.9%, 9.5% and 0.64 nm, respectively.